THE IMPLEMENTATION OF âARIASâ STRATEGY TO INCREASE STUDENTSâ SPEAKING SKILL AT SMA NEGERI 1 BUNGORO - Sangkala, Ismail (Lembaga Perpustakaan Unismuh Makassar, 2012)
The Implementation of âARIASâ Strategy to Increase Studentsâ Speaking Skill at SMA Negeri 1 Bungoro. The objective of the research is intend to know the increasing of the studentsâ accuracy and fluency in speaking through ARIAS strategy at third year studentsâ of SMA Negeri 1 Bungoro. The method of this research is classroom action research consist of two cycles. Both of cycles consist of four meetings. It means that there are eight meetings for two cycles. The subject in this research is X.3 Senior High School in 2011-2012 academic years. That consists of 17 women and 35 men. Instruments are speaking test and observation.Keywords: Speaking, Assurance, Relevance, Interest, Assessment, Accuracy, Fluency and Satisfaction.Penerapan Strategi